Turning the Tide : Saving Fish and Fishers - World Bank (Washington, DC, 2014)
The Millennium Ecosystem Assessment, the first global assessment of the state of the world's ecological health, published in March 2005, identified global fisheries as one of fi ve global systems in critical condition. This paper is one of many studies that show how on local, regional, and global scales, fish are taken out of the sea far faster than many existing fishstocks can replenish themselves. The World Bank Group recognizes that it is time for a proactive, international approach to improve the fisheries sector worldwide. The challenge in moving toward a sustainable fishing industry is to maintain economic growth and development by enhancing productivity and the wealth of fisheries, while avoiding the overfi shing and ecological degradation that we see today. The World Bank Group's current efforts concentrate on coastal management, inland fisheries, and smallholder aquaculture operations, mostly in developing countries in Africa and East Asia. The World Bank Group will broaden its support for sustainable fisheries at country, regional, and global levels, and is establishing a new Global Program for Sustainable Fisheries (PROFISH). This program will focus on good governance, sustainable fisheries policies, and the promotion of effective fisheries strategies. In cooperation with the Global Environment Facility (GEF), the World Bank Group is participating in regional fisheries initiatives, such as the Strategic Partnership for Sustainable Fisheries in Sub-Saharan Africa, and building on GEF's large marine ecosystem projects.